A multi-agent brokerage platform for media content recommendation - Veloso, Bruno; Malheiro, Benedita; Burguillo, Juan Carlos (Zielona Góra: Uniwersytet Zielonogórski)
Near real time media content personalisation is nowadays a major challenge involving media content sources, distributors and viewers. This paper describes an approach to seamless recommendation, negotiation and transaction of personalised media content. It adopts an integrated view of the problem by proposing, on the business-to-business (B2B) side, a brokerage platform to negotiate the media items on behalf of the media content distributors and sources, providing viewers, on the business-to-consumer (B2C) side, with a personalised electronic programme guide (EPG) containing the set of recommended items after negotiation.
Keywords: multi-agent computing; brokerage platform; media content personalisation; recommendation